Class II phosphatidylinositol 3-kinase-C2α is essential for Notch signaling by regulating the endocytosis of γ-secretase in endothelial cells - Shota Shimizu; Kazuaki Yoshioka; Sho Aki; Yoh Takuwa (Scientific Reports, 2021)
Abstract The class II α-isoform of phosphatidylinositol 3-kinase (PI3K-C2α) plays a crucial role in angiogenesis at least in part through participating in endocytosis and, thereby, endosomal signaling of several cell surface receptors including VEGF receptor-2 and TGFβ receptor in vascular endothelial cells (ECs). The Notch signaling cascade regulates many cellular processes including cell proliferation, cell fate specification and differentiation. In the present study, we explored a role of PI3K-C2α in Delta-like 4 (Dll4)-induced Notch signaling in ECs. We found that knockdown of PI3K-C2α inhibited Dll4-induced generation of the signaling molecule Notch intracellular domain 1 (NICD1) and the expression of Notch1 target genes including HEY1, HEY2 and NOTCH3 in ECs but not in vascular smooth muscle cells. PI3K-C2α knockdown did not inhibit Dll4-induced endocytosis of cell surface Notch1. In contrast, PI3K-C2α knockdown as well as clathrin heavy chain knockdown impaired endocytosis of Notch1-cleaving protease, γ-secretase complex, with the accumulation of Notch1 at the perinuclear endolysosomes. Pharmacological blockage of γ-secretase also induced the intracellular accumulation of Notch1. Taken together, we conclude that PI3K-C2α is required for the clathrin-mediated endocytosis of γ-secretase complex, which allows for the cleavage of endocytosed Notch1 by γ-secretase complex at the endolysosomes to generate NICD1 in ECs.